Agnurodesmus siolii n.sp., the first Cyrtodesmidae to be reported from Brazil, with remarks on the genus and family (Diplopoda, Polydesmida) - Golovatch, Sergei I. (Amazoniana, 2001)
A new species of Cyrtodesmidae is described from a terra firme tropical rainforest patch near Manaus, Central Amazonia of Brazil: Agnurodesmus siolii n.sp
Keywords: Cyrtodesmidae